Exploring literary competences in EFL preservice teachers’ pedagogical proposals - Gabriel Romero Karlsson; Malba Barahona (Cogent Education, 2024)
This study investigates the development of literary competences among EFL preservice teachers (PSTs) through their engagement with picturebooks in an EFL teacher education program in Santiago, Chile. Using qualitative content analysis, the study examines the pedagogical proposals and reading sessions of 12 PSTs to identify the types of literary competences they developed. The findings reveal that while PSTs demonstrated strengths in plot and character analysis competence and subjective and emotional competence, they showed less proficiency in thematic and symbolic competence, esthetic and stylistic competence and cultural competence. However, the results highlight the potential of integrating picturebooks into EFL classrooms to foster diverse literary competences. The paper concludes suggesting that EFL teacher education programs should adopt a balanced approach, incorporating both text-oriented and reader-oriented activities to better prepare English teachers for effective literary instruction.